Polifonia e hibridismos musicais: relações dialógicas entre Luiz Gonzaga, Gilberto Gil e Torquato Neto - Moraes, Jonas Rodrigues de (2014)
This research aims to discuss and analyze the musical production, dialogism and the interrelationships between the composer Luiz Gonzaga (1912-1989) and artists Gilberto Gil (1942) and Torquato Neto (1944-1972). The aesthetic universe and the evolution of artists under discussion are investigated through the processes of polyphony, territorialization, hybridization, performance, among other postulates - categories that constitute important bases for the construction of this work. Another relevant approach in this study is the relentless pursuit of reviewing the processes of invention and institution of territorial identity markers from the Northeast region through the interrelation between universal and local in the compositions of the three artists. Luiz Gonzaga acquired projection from the reinvention of the baião, but the accordionist from Araripe also appropriated himself from other musical rhythms, which exercised discursive and decisive functions for the institutionalization of the Northeast and the Northeastern people. Thus, the gonzaguean sonority had the ability to express a feeling of nordestinity, which reverberated and found resonance in their listeners/receivers. This proposal also seeks to understand how artists Gilberto Gil and Torquato Neto - members of the Tropicalia movement - appropriated themselves from the gonzaguean musical universe and of the genres regarded as coming from the Northeast, as well as other soundscapes. It is understood that in the songs from these composers there is a visible dialogue with the modus operandi of Luiz Gonzaga, when it comes to rhythms, performance, melodic elements, textual, as well as signs that refer to the acoustic culture of the northeastern hinterland. It aims, accordingly, at investigating, in the relation of the history with the music, the dialogism and polyphony and hybridization processes in the songs of such composers